Perancangan Sistem Pemantau Keamanan Rumah Dengan Sensor Pir dan Kamera Berbasis Mikrokontroler dan Internet Of Things (Iot) - Redo Dwi Putra; Riki Mukhaiyar (Dinasti Research, 2022)
The recent increase in crime is wrong a result of the economic crisis. Especially during the Covid-19 outbreak, people's economic activities were limited. Apart from the health sector, the Covid-19 outbreak has affected the economic sector, especially the sustainability of activities and income. The impact of the Covid-19 pandemic has led to a potential increase in crime due to economic demand pressures, in 2020 the number of theft and theft with violence in households is 1,628,634. This final project aims to design a Home Security Monitoring system with Pir Sensors and Microcontroller-Based Cameras and the Internet of Things using the ESP32-CAM type as a microcontroller for the control center. The PIR sensor functions to send notifications to users when it detects movement, then the OV2640 camera will take photos and videos and then send the results to the operator via smartphone using the Telegram bot application to monitor activities at home. This test results that the maximum distance that can be detected by objects is 6 meters. Testing the entire system that has been carried out proves that the system is able to work in detecting, recording and sending the results to the user. The time required for sending object detection photos and videos is 4.7 seconds and 40.7 seconds.